Daily Mobility in Metropolitan Areas: The case of higher education students and urban spatial development in the Valparaiso Metropolitan Area - Soto Caro, Marcela (A+BE | Architecture and the Built Environment, 2024)
This study seeks to understand the interrelationship between daily mobility and the spatial structure of an emerging metropolitan urban system. It is concerned with the daily mobility of a specific group of inhabitants, higher education students, living in a contemporary metropolis and experiencing urban living. The study’s main aim is to better understand aspects of this complex urban spatial structure through the students’ lives and through their daily mobility to explore specific urban spatial dynamics and trends. This study therefore considers the effects of an accelerated urbanisation process and the development of an increasingly fragmented and segregated socioeconomic environment. In doing so, it highlights the ways in which rapid urban expansion in developing countries has tended to reproduce or maintain a range of inequalities. The study is built on the assumption that daily mobility can be understood as the sum of individual movements in the city. This socially enabled practice allows individuals to access people, places, and activities through urban space and time. This way of understanding mobility responds to the recent “mobility turn” within the social sciences. This change in thinking posits that ‘movement’ is a significant an actor of change. It explores changes to the urban spatial structure and their impact on the inhabitants. It tries to understand how changing urban structures are experienced by those living in those urban spaces. In this study, how the student population lives, works, studies, and spends its leisure time within the Valparaiso Metropolitan Area (VMA) proves to be dependent on a complex of structural factors. These include, for example, the locations where these activities are performed, the socioeconomic background of those performing such activities and the distribution of university facilities within a metropolis which has a particular and distinctive topography. Such day-to-day activities are further shaped by more dynamic and perhaps more subtle influences such as the changing functions of the urban space, increasing socioeconomic fragmentation and segmentation and the inequitable provision of public transport across what is a topographically complex area. The collection and analysis of data, including empirical surveys and interviews, was informed by Kaufmann’s three conditions for mobility, Competence, Appropriation and Access. Competence covers an individual’s physical abilities and the skills they acquire, Appropriation encompasses the range of mobility strategies used by individuals and Access, a condition that refers to the variety of potential mobilities that confront an individual according to place, time, and other structural constraints (Kaufmann, 2012). Kaufmann argues that together all three conditions determine the capital of mobility that students have as they go about their daily lives but also defines how an individual or groups of individuals take advantage of existing mobility options and uses them to create a lifestyle (Kaufmann, 2012). A range of research methods has been used to examine the student’s daily mobility patterns in this study. In order, these methods include: (1) Documentary and other secondary data which has been used to understand changes to existing metropolitan structure over three decades; to understand urban spatial conditions related to urban mobility, higher education and urban development, and explain the spatial distribution of Traditional Universities within the VMA; (2) Empirical methods including face-to-face structured interviews with higher education students and an extensive internet survey have been use to enrich the data gathered in the first phase, finally (3) data drawn from the initial survey work, together with data gathered from the in-depth interviews have been combined with mapping other secondary data to confirm and extend existing sources. The internet survey results (824 students) provided further essential data on a range of individual’s travel patterns from different parts of the metropolis. Three primary patterns of mobility emerged from this study of the student daily mobility: those related to local, regional migrant, and national migrant students. The three mobility patterns can be explained first by looking at the residential conditions, whether individual students are locals or migrants, and from which region they are coming. This latter condition influences the choices of migrant students when it comes to housing location. During the study, it was discovered that regional migrants tend to live around central areas whereas national migrants prefer to be nearer the university campus. By contrast, local students are not so free to choose, and consequently, they live all around the metropolitan area. The daily mobility patterns of local students (70%) consisting mainly of long trips to the centre tend to mirror general trends in the structural development of the VMA. A range of influences have tended to promote peripheral growth and conversely, the increasing abandonment and decline of the historic urban centre. Running counter to this socially polarised outward flow, characteristic of neoliberal economic policies and post-Fordist processes, there are signs of a returning flow towards the historic centre. This weak but increasingly visible return to the centre is a perhaps a consequence of the policies actively pursued by the area’s traditional higher education institutions. The daily mobility patterns of the migrant students surveyed (39%) demonstrates the presence of this weak but important returning flow. Their preference for living in near to their places of study highlights the relationship between the (re)development of central metropolitan spaces and the comparatively higher levels capital for mobility available to migrant students. Finally, even though it is recognised that travel times are longer for all local students independent of their socioeconomic condition, the data for local low-income students provides some important qualifications. The low-income groups of local students who live in high-hill areas with limited connectivity to central areas of the VMA notably must endure extended trips between their homes and their study places. It is therefore demonstrated that levels of capital for mobility for this specific group is associated with significant social differentiation. The research has further revealed that a lack of a comprehensive infrastructure network in the metropolis’s interior means that a significant population living above 100 m.a.s.l by necessity often must develop distinctive and complex daily mobility strategies. The paradox in these cases, lies between the growth rate and the infrastructure deficit. Another critical problem revealed by the study is the continuing deterioration and underuse of central historical areas. The research suggests that higher education institutions might now play an essential role in reversing these trends particularly if supported by robust public policies. More broadly, the extent literature has tended to reduce the scale of analysis of daily mobility to neighbourhoods. This research within this study however demonstrates that a better understanding of an individuals’ daily mobility can make visible urban trends that have previously been left undisturbed by the existing traditional origin and destination surveys. The research therefore serves to highlight the social and economic flows that continue to shape the metropolitan spatial structure.